Метод чисельного аналізу нестаціонарних в’язких течій у областях з рухомою межею - Полковніченко, Є. Ю. (ХНУРЕ, 2019)
The problem of the numerical analysis of the unsteady flow of a viscous incompressible fluid in a bounded area with a moving boundary is considered. For its numerical analysis it is proposed to use the principle of superposition, the R-functions method with approximation of the uncertain component using the nonlinear Galerkin method.
Keywords: нестаціонарні в'язкі течії; область з рухомою межею; нелінійний метод Гальоркіна; в'язка нестислива рідина